Examining the influence of hide processing on Native American upper limb morphology. (17th April 2018) - Cameron, M.E.; Lapham, H.; Shaw, C.
Abstract: The commercial pelt trade between Native Americans and Europeans flourished in the 17th and 18th centuries. However, the impact of this economic change and increased hide processing efforts on Native American upper limb morphology is unknown. The hide scraping hypothesis, tested in living subjects, suggests that hide processing efforts may lead to significant changes in humeral morphology. Two modern human Native North American skeletal collections from south‐western Virginia, USA, were studied to test if intensive hide processing led to changes in humeral morphology. At the earlier Late Woodland Crab Orchard site, animal skins and furs were prepared for household use. During the occupation of the later early historic Trigg site, processing activities intensified to produce surplus hides for the commercial pelt trade. In this study, the cross‐sectional geometric properties at the mid‐distal humerus (35% of length) of Crab Orchard and Trigg adult males and females were examined. We assessed whether Trigg site individuals had increased humeral symmetry, changes to diaphyseal shape, and increased robusticity. Additionally, humerus morphological properties were compared between males and females to assess if there were sex‐based differences. Trigg site males had greater humeral robusticity than Crab Orchard males. The humeri of females from the Trigg and Crab Orchard sites were both relatively anteroposterior strengthened and displayed quite low levels of bilateral asymmetry. This pattern suggests that females at both sites may have employed techniques that involved bimanual hide processing tools. The differences between the morphologies predicted and those observed in these Native American populations may indicate (a) adaptation to bimanual hide processing techniques or (b) adaptation to osteogenic tasks not involved in hide processing but associated with postcontact economic changes.